Geoinformação e setor público: uma avaliação da Produção Científica utilizando ferramentas de mapeamento da ciência - Gianordoli, Victor (2016)
This research explores how tools that support bibliometric studies (VOSviewer and CitNetExplorer) allow the mapping of scientific knowledge through international journals, available at the Web of Science database, according to criteria defined and shown in the field of geo- information, in the public sector. This paper is divided in the following sections: theoretical framework related to geo-information and its contextualization in the public sector; bibliometrics; tools for mapping science, where one analyzes the possibilities for mapping scientific knowledge and the ProKnow-C method. In the section about bibliometrics, one deals with the definitions related to metrics of academic outcomes, from its origin until today, where technology allows the analysis of samples using a great amount of data. Using maps of networks, bibliometric studies (co-authorship, co-occurrence, citation, bibliographic coupling, co- citation and data mining) and scores of tools, one could present the current stage of geo-information applied to the public sector, highlighting the main authors, works, organizations, funding agencies, countries and fields of knowledge. The field of Health was the most prominent in the universe studied. One concludes that, among the various possibilities for analysis, the ones which used these tools were more advantageous and that the methodology used here showed the connection between geo-information and the public sector. This research is relevant for the academia, because its theme is related to geo-information and the public sector, and because it is a proposal for a methodology that uses tools for presenting bibliometric results. Moreover, it promotes the graduate program in which this research was developed, since it presents tools for bibliometric analysis for mapping science, and it could be used for other works of research, which require a comprehensive view about a certain field of knowledge, and for the discipline “Geo-information in the Public Sector”